SUBSTANTIVE CRIMINAL LAW OF THE MEDICRIME CONVENTION AND CRIMINAL LEGISLATION OF BOSNIA AND HERZEGOVINA - RELATIONSHIP BETWEEN HARMONY OR NON-COMPLIANCE - Novaković, Filip (Glasnik Advokatske komore Vojvodine, 2023)
The trade in counterfeit medical products is a growing global criminal industry (especially in the field of organized crime), which poses a great threat to individuals, ie patients, but also to health systems. Circulation and sale of counterfeit medical products is carried out through unregulated channels (along the road, in the market, via the Internet, and even in bars, nightclubs and bakeries). The Council of Europe Convention on Counterfeiting of Medical Devices and Similar Offenses, which involves threats to public health, is the first international treaty of its kind, an international instrument establishing a legal framework to combat the production and trafficking of counterfeit medicinal products and this criminal black market. It provides for the criminalization of certain acts, provides for special provisions related to criminal procedure, protects the rights of victims of criminal acts and promotes national and international cooperation in criminal matters.